Dukung Program Vaksinasi COVID-19 pada Ibu Hamil dan Ibu Menyusui: Dukung Program Vaksinasi COVID-19 pada Ibu Hamil dan Ibu Menyusui - Vella Yovinna Tobing; Dian Roza Adila; Eva Nurlis (STIKes Hang Tuah Pekanbaru, 2022)
The spread of the COVID-19 virus is global. It is currently rumored that the virus has mutated and become more dangerous. One way that can be done to prevent transmission of the virus is to strengthen the body's defense system through vaccination. Several issues have caused the COVID-19 vaccination program to receive pros and cons. The contra conditions are due to doubts regarding the safety and effectiveness of the COVID-19 vaccination. This doubt especially arises in the group of pregnant and lactating women, so that the coverage of the COVID-19 vaccine for the group of pregnant and lactating women is still not optimal. Education related to COVID-19 vaccination for pregnant and lactating mothers is one of the challenges, especially during the pandemic where there are restrictions on the length of visits during ANC. Based on the results of a preliminary study at the Rumbai Bukit Health Center, there is no educational media regarding the COVID-19 vaccine for pregnant and lactating women that patients can take home. In addition, health workers experience limited time because the majority of health workers also play a role as vaccinators. Therefore, this activity aims to assist the government in socializing the vaccination program in the form of making booklets containing information about vaccinations for pregnant and lactating women. This booklet is expected to be an educational medium and a source of information related to COVID-19 vaccination that can be read at home by patients and their families. This activity received appreciation and positive response from the Coordinator Midwife at the Rumbai Bukit Health Center Pekanbaru City. The media in the form of this booklet will greatly assist the patient education process, especially pregnant women. Abstrak Penyebaran virus COVID-19 terjadi secara global. Saat ini dikabarkan bahwa virus sudah bermutasi dan menjadi lebih berbahaya. Salah satu cara yang dapat dilakukan untuk mencegah terjadinya penularan virus adalah dengan memperkuat sistem pertahanan tubuh melalui vaksinasi. Beberapa issue menyebabkan program vaksinasi COVID-19 mendapat tanggapan pro dan kontra. Kondisi kontra dikarenakan adanya keraguan terkait keamanan dan keefektifan vaksinasi COVID-19. Keraguan ini khususnya timbul pada kelompok ibu hamil dan menyusui, sehingga cakupan vaksin COVID-19 untuk kelompok ibu hamil dan menyusui masih belum optimal. Edukasi terkait vaksinasi COVID-19 pada ibu hamil dan menyusui menjadi salah satu tantangan, terutama dimasa pandemi dimana adanya pembatasan lama kunjungan saat melakukan ANC. Berdasarkan hasil studi pendahuluan di Puskesmas Rumbai Bukit, belum ada media edukasi terkait vaksin COVID-19 pada ibu hamil dan menyusui yang bisa dibawa pulang oleh pasien. Selain itu, tenaga keseshatan mengalami keterbatasan waktu karena mayoritas tenaga kesehatan juga berperan menjadi vaksinator. Oleh karena itu, kegiatan ini bertujuan untuk membantu pemerintah dalam mensosialisasikan program vaksinasi berupa pembuatan booklet yang berisi info tentang vaksinasi pada ibu hamil dan menyusui. Booklet ini diharapkan dapat menjadi media edukasi dan menjadi sumber informasi terkait vaksinasi COVID-19 yang bisa dibaca di rumah oleh pasien dan keluarga. Kegiatan ini mendapatkan apresiasi dan tanggapan yang positif dari Bidan Koordinator di Puskesmas Rumbai Bukit Kota Pekanbaru. Media berupa booklet ini akan sangat membantu proses edukasi pasien, terutama ibu hamil.